Can local products compete against imports in West Africa? Supply-and demand-side perspectives on chicken, rice, and tilapia in Accra, Ghana - Andam, Kwaw S.; Ragasa, Catherine; Asante, Seth; Amewu, Sena (International Food Policy Research Institute, 2019)
This paper examines the prospects for import substitution in West Africa by analyzing the preferences of urban consumers for food product attributes. We use market surveys, choice experiments, and experimental auctions to assess price and quality competitiveness of locally-produced chicken, rice, and tilapia in Accra, Ghana. For the price analysis, we compare market prices of imported and local counterparts, and we compare the local costs of production to production costs in major exporting countries. For the quality analysis, we compare consumer perceptions and demand for quality attributes of local versus imported products using data from field experiments with 1,322 consumers. Our findings suggest that among the three products, rice has the lowest prospects for import substitution, due to supply-and demand-side constraints to local competitiveness. For rice, consumers prefer imported products, they perceive imports as having better quality than local products, and they are willing to pay a premium for imports. For chicken, consumers have a strong preference for local products, but the potential for expanding chicken production can only be met if production and processing costs can be reduced significantly to boost price competitiveness. For tilapia, a high preference for freshness provides a natural barrier to import entry, and the comparative advantage of local production can be enhanced by making continuous improvements in seed and extension systems, industry coordination, certification, and regulation.